Synthesis & Characterization of Oxazinan and 5-oxa-7-aza-spiro[2,5] octane from reaction of Dibenzylidene with malonic anhydride and 5-oxa-spiro[2,3] hexane-4,6-dione. (Baghdad Science Journal, 2007)
Di Benzylidenes were prepared by condensation of 1,2-diamino benzene with o- hydroxy benzaldehyde. These dibenzylidenes when treated with one equivalent of malonic anhydride or 5-oxo-spiro[2,3]hexane-4,6-dione in dry benzene give 6-membered heterocyclic ring system of 3-{2-[(2-Hydroxy-benzylidene)-amino]-phenyl}-2-(2-hydroxy –phenyl)-[1,3]oxazinane-4,6-diones ( 1-3) or 7-{2-[(2-hydroxy-benzylidene)-amino]-phenyl}-6-(2-hydroxy-phenyl)-5-oxa-7-aza-spiro[2.5]octane-4,8-diones ( 7- 9 ) But when two equivalents of malonic anhydride or 5-oxo-spiro[2,3]hexane-4,6-dione were used and under sam conditions compounds (4-6 , 10-12 ) were obtained .